Boolean Centre of a C-algebra - Kalesha Vali, Shaik; Sundarayya, P.; Swamy, U.M. (Armenian Journal of Mathematics, 2011)
There is a precise characterisation of factor congruences on a C-algebra with meet identity T. The characterisation of such congruences on a C-algebra with out T is a difficult task. In this paper, we make such an attempt and we characterise the factor congruences on a C-algebra A and identify these with certain elements or sets of elements of A.